2018
DOI: 10.1038/s41598-018-19533-5
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Diaphorina citri Kuwayama (Hemiptera: Liviidae): host-driven genetic differentiation in China

Abstract: The Asian citrus psyllid Diaphorina citri Kuwayama is a major pest in citrus production, transmitting Candidatus Liberibacter asiaticus. It has spread widely across eastern and southern China. Unfortunately, little is known about the genetic diversity and population structure of D. citri, making pest control difficult. In this study, nine specifically developed SSR markers and three known mitochondrial DNA were used for population genetics study of D. citri using 225 samples collected from all 7 distribution r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…Jiangxi, Zhejiang and Hunan are relatively newly invaded areas and the CLas populations there have greater prophage‐associated gene diversity. Greater genetic diversity was also detected in ACP in these provinces (Meng et al , ). This strongly suggests that CLas in these areas has experienced a series of recent population expansion events through introductions of infected seedlings from multiple diseased provinces (Huang, ; Ganzhou Citrus Huanglongbing Research Group, unpublished investigation report on occurrence and distribution of citrus huanglongbing in 1979; Institute of Subtropical Crops, Zhejiang Academy of Sciences, unpublished investigation report of citrus huanglongbing in 1982), multiple invasions of ACP, the recent rapid diversification of citrus varieties and extensive commercial cultivation of citrus trees in recent years (Meng et al , ).…”
Section: Discussionmentioning
confidence: 87%
“…Jiangxi, Zhejiang and Hunan are relatively newly invaded areas and the CLas populations there have greater prophage‐associated gene diversity. Greater genetic diversity was also detected in ACP in these provinces (Meng et al , ). This strongly suggests that CLas in these areas has experienced a series of recent population expansion events through introductions of infected seedlings from multiple diseased provinces (Huang, ; Ganzhou Citrus Huanglongbing Research Group, unpublished investigation report on occurrence and distribution of citrus huanglongbing in 1979; Institute of Subtropical Crops, Zhejiang Academy of Sciences, unpublished investigation report of citrus huanglongbing in 1982), multiple invasions of ACP, the recent rapid diversification of citrus varieties and extensive commercial cultivation of citrus trees in recent years (Meng et al , ).…”
Section: Discussionmentioning
confidence: 87%
“…Although sequences of cox1 have commonly been used in phylogenetic studies of ACPs, our whole mitogenome sequence analyses showed that resolution of cox1 sequences is limited for ACP. In fact, no diversity was detected using cox1 among Chinese ACP samples in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S2a). A recent study reported the detection of SNPs in cox1 from ACPs collected in China . Reasons for the differences remain to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations